Antiarthritic efficacy of Clematis orientalis - Hasan, Umme Habiba; Alamgeer, . (Bangladesh Journal of Pharmacology, 2018)
Clematis orientalis has been used traditionally to cure rheumatism, but its efficacy has not been scientifically explored in treating rheumatoid arthritis. The present study was designed to investigate the antiarthritic efficacy of C. orientalis using blockade of heat-induced protein alterations and HRBC membrane stabilization methods along with formaldehyde induced arthritis in rats. Aqueous ethanol (30:70) extract and various fractions (hexane, n-butanol and aqueous) produced concentration-dependent and significant (p<0.001) inhibition of protein (egg albumin and bovine serum albumin) denaturation and red blood cell membrane stabilization at 50-6400 ug/mL concentration. Similarly in formaldehyde induced arthritis plant extract and fractions revealed the considerable reduction in paw swelling and its diameter at doses of 50, 100 and 200 mg/kg with maximum (p<0.001) effect at the highest dose. Thus present findings imply that aqueous ethanol extract as well as different fractions of C. orientalis has noteworthy antiarthritic potential supporting its folkloric use in inflammatory arthritic conditions.